A Study on Investors' Perception towards Mutual Funds other than Non Risky Investment Avenues (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2018)
An old short saying "United we stand, divide we fall" works today to help small investors by  investing in mutual funds as it help them to stand united, reducing risk by diversification and to  provide higher returns in comparison to traditional non risky investment avenues. In the current  era a retail investor has many options available to invest his money to get future return according  to their goals and risk bearing capacity which varies from old traditional schemes to newly launched  various schemes. It has been found from the previous past studies that small and medium retail  investors are still investing majority of their surplus in banks, post office and other traditional  investment options which is not providing them real higher returns. Some of them are taking risk  and investing in risky securities but because of less understanding of market they got losses from  direct market investments. As a solution Mutual Fund is the best investment option which is available  to a retail investor which provides higher return then traditional investment options with availability  of multiple level of diversification and managed by professional expert fund managers which help  in reducing risk too. It has been seen that mutual funds hove outperformed in the long run by  giving persistent higher returns but still captured very less percentage of the market due to lack of  awareness and familiarity. The objective to this paper is to explore how mutual fund is a better  investment option in current era and understanding of Investor's perception towards Mutual Fund  investments other than Non Risky Investment avenues. Primary data from structured questionnaire  and secondary data from various sources have been collected and used in this research. The  study further help in understanding the comparison between mutual fund and various other  investments. The study reveals that those retail investor who have invested in mutual funds are  satisfied and get good returns as compared to other traditional investment options but still there  is a requirement of more understanding. The paper suggests that by spreading awareness and  making digital availability of mutual fund investment can help in tapping more investors so as to  provide higher return and fulfill their objectives and setting the mutual fund industry growth path.
Keywords: Mutual Fund; Retail Investor; Investment; High Return